Oil-led economic growth and the distribution of real household incomes and consumption in Azerbaijan - Mateusz Walewski; Alexander Chubrik (Center for Social and Economic Research (CASE), 2010)
This paper analyzes the distribution of real household incomes and consumption growth in Azerbaijan between 2004 and 2009. Decile-specific price deflators were used to calculate real incomes and consumption dynamics. The analysis, which was based on growth incidence curves, showed that economic growth between 2004 and 2009 was definitely propoor, both for real incomes and real consumption. Our results also indicate that household incomes were much more strongly correlated with oil GDP than with non-oil growth. Employment was the most important source of income growth for all deciles. Poorer households changed their coping strategies from subsistence agriculture to paid- and selfemployment. Although this led to a dynamic increase in their incomes, it hardly changed their consumption basket, with food still constituting more than 65% of spending. This means that their actual standard of living level did not change very much. Our results also indicate the low effectiveness and efficiency of social transfers; they were found to be almost evenly distributed among income deciles and played a negligible role in the income growth of the poorest households.
Keywords: D31; 330; Azerbaijan; poverty; growth incidence curves; economic growth; Armut; Haushaltseinkommen; Einkommensverteilung; Privater Konsum; Wirtschaftswachstum; Aserbaidschan